2017
DOI: 10.1136/bmjinnov-2016-000184
|View full text |Cite
|
Sign up to set email alerts
|

Innovation for the future of Irish MedTech industry: retrospective qualitative review of impact of BioInnovate Ireland’s clinical fellows

Abstract: Clinicians have historically been integral in innovating and developing technology in medicine and surgery. In recent years, however, in an increasingly complex healthcare system, a doctor with innovative ideas is often left behind. Transition from idea to bedside now entails significant hurdles, which often go unrecognised at the outset, particularly for first-time innovators. The BioInnnovate Ireland process, based on the Stanford Biodesign Programme (Identify, Invent and Implement), aims to streamline the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Previous studies have identified that successful innovations require internal champions at every step of the innovation timeline to move them forward ( 34 ). A PRIME would take this one step further and obviate the need for individuals to move against the grain.…”
Section: Spatial and Temporal Axes Of Innovationmentioning
confidence: 99%
“…Previous studies have identified that successful innovations require internal champions at every step of the innovation timeline to move them forward ( 34 ). A PRIME would take this one step further and obviate the need for individuals to move against the grain.…”
Section: Spatial and Temporal Axes Of Innovationmentioning
confidence: 99%